Response of Crop Rotations to Sodie Waters and Amendments in Loamy Sands of Southern Haryana - Singh, Satyavir; Singh, Sultan; Kumar, Parmod; Tikkoo, Abha (Annals of Arid Zone, 2016)
A long term experiment was carried out to evaluate the effect of sodic waters (RSC 2.8, 12.0 and 16.0 me L-’) and amendments (gypsum applied @ 100% neutralization of RSC above 2.8 me L-1 and FYM applied at @ 15 tonnes ha-1 year"l) on the productivity of various cropping systems and physico-chemical characteristics of the loamy sand, typic Ustrocrept. The crop rotations were sorghum fodder-mustard, sorghum fodder-wheat, prickly sesbane-wheat and pearl millet-mustard, each rotation continued for three years. Progressive buildup of sodicity (ESP) and soil pH with low infiltration rate was observed with water of higher alkalinity (RSC 12 and 16 me L- The gypsum maintained the ESP and pH of the soil and increased the infiltration rate. The FYM was more beneficial with irrigation water of RSC 2.8 me L-1 . Crop yields decreased significantly with increasing sodicity of the irrigation water. Sodic water of RSC 12 me L-1 with gypsum produced yields statistically equal to that of irrigation water of RSC 2.8 me L-l in pearl millet, wheat, mustard, prickly sesbane and sorghum. Sodic water of RSC 16 me L-1 with both amendments was not found effective. FYM as an amendment increased the crop yields, but was inferior to gypsum under high sodic water condition (RSC 12 and 16 me C’). In general, sodic water of RSC 12 me L-1 along with gypsum can be successfully used in sorghum fodder-mustard, sorghum fodder-wheat. prickly sesbane-wheat and pearl millet-mustard crop rotations in light textured soils. Key words: Brackish, sodic waters, crop rotation, RSC, amendment.